Implementasi Manajemen Mutu Pendidikan di Sekolah Islam: Implementation of Educational Quality Management in Islamic Schools - Febrina, Mira; Sesmiarni, Zulfani (Thawalib: Jurnal Kependidikan Islam, 2024)
Quality management in education is crucial to improving the quality of Islamic education, especially in private Islamic schools. This study identifies the implementation, challenges, and solutions for quality management in education at Al Azhar Islamic School in Bukittinggi. The research method used is a case study with a qualitative approach. Data collection techniques include interviews, observation, and analysis of relevant documents. Data analysis is processed through reduction, presentation, and verification to draw conclusions, with data validation using triangulation. The results of the study show that there are several stages or phases in the implementation of quality management in Islamic education at Al Azhar Islamic School. The first phase is the preparation phase of quality management, which includes forming a quality management team, stating the vision and principles as guidelines, and conducting a strengths and weaknesses analysis. The second phase is the planning phase of quality management, which includes planning the implementation of quality management in education and forming a management implementation team. The third phase is the implementation phase of quality management, which includes teaching processes, learning evaluation, resource management, and program monitoring and evaluation.